Case Report: Neonatal Massive Pneumothorax Resulting in Compression Atelectasis Treated by Ultrasound-Guided Pleural Puncture Therapy: A Typical Case Based on Lung Ultrasound Finding - Liu, Jing; Qiu, Ru-Xin; Liu, Ying (Frontiers in Pediatrics, 2021)
Atelectasis is a complication of different pulmonary diseases; however, neonatal compression atelectasis due to pneumothorax is rarely reported in the literature. Recently, we encountered a typical case of atelectasis. A preterm infant was admitted to the neonatal intensive care unit owing to severe respiratory distress. Lung ultrasound examination confirmed severe pneumothorax and large area of atelectasis. Lung re-expansion occurred when the air was drained from the pleural cavity.